A Neural Network Approach to Synthetic Control Chart for the Process Mean - Khoo, Michael Boon Chong; Low, Heng Chin; Ong, Hong Choon (Universiti Sains Malaysia, 2010)
In this project, a multivariate synthetic control chart for monitoring the process mean vector of skewed populations using weighted standard deviations has been proposed. The proposed chart incorporates the weighted standard deviation (WSD) method of Chang and Bai (2004) into the standard multivariate synthetic chart of Ghute and Shirke (2008).